ASSESSING THE DISTRIBUTION OF SELF-PAYING INNOVATIVE ONCOLOGY MEDICINES AMONG CANCER PATIENTS - Dzulkipli, Mohd Redhuan; Shafie, Asrul Akmal; Maon, Siti Noorsuriani; Ramli, Azuana; Mohammad Yahaya, Abdul Haniff; Ho, See Wan; Muhsin, Nor Ilham Ainaa; Ahmat, Azmi Nor Mohd Farez (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: Innovative oncology medicines offer advanced cancer treatment but often come with high costs, limiting access through public healthcare funding. Aims: This study examines the distribution of self-paying innovative cancer drugs among patients in Malaysian public hospitals. Methods: Using oncology pharmacy records from 2017 to 2020, 157 patient samples were collected, constrained by COVID-19 restrictions. Results: The average patient age was 57 years (SD= 11.47), with a predominance of females (73.9%) and Chinese ethnicity (48%). Breast cancer was the most common diagnosis (47%), followed by lung (17%) and colon cancer (10%). Frequently prescribed drugs included Trastuzumab, Palbociclib, Osimertinib, Cetuximab, and Bevacizumab, most of which are listed in the Ministry of Health’s Formulary of Listed Anticancer Drugs (FLAD). Patients paid an average annual cost of MYR 16,233.90 (SD= 20,424.67) for FLAD medicines and MYR 11,239.75 (SD= 122,793.50) for non-FLAD medicines. Conclusion: The study highlights that out-of-pocket payments are the primary funding source for these treatments, posing significant financial burdens and potential long-term economic strain on cancer patients in Malaysia. Keywords: FLAD, Funding Mechanism, Innovative Oncology Medicine